Shooting at Moving and Hidden Targets-Tumour Cell Plasticity and the Notch Signalling Pathway in Head and Neck Squamous Cell Carcinomas - Kalafut Joanna; Czerwonka Arkasiusz; Anameric Alinda; Przybyszewska-Podstawka Alicja; Misiorek Julia O; Rivero-Mueller Adolfo; Nees Matthias (MDPI, 2022)
Simple Summary Cancers in the head and neck region are often aggressive and poorly respond to both irradiation or chemotherapy. Chemotherapy is currently limited by a small number of approved drugs. Newer "targeted" drugs, aiming for specific molecules expressed by tumour cells, have not been as beneficial as expected. Research is now investigating new drug targets, involved in the way how tumour cells interact with non-cancer cells from the stroma, the vasculature, and the immune system within the tumour tissues. These highly dynamic processes assist tumour cells to rapidly adapt to any challenges they may encounter during cancer progression or therapy. One such central molecular mechanism, regulating increased tumour cell plasticity, is the Notch signalling pathway. We currently are only beginning to understand the complex interactions of Notch receptors with their ligands, in a broad spectrum of tumour and tumour-associated cells, and how such interactions could represent targets for cancer chemotherapy and personalized medicine. Head and Neck Squamous Cell Carcinoma (HNSCC) is often aggressive, with poor response to current therapies in approximately 40-50% of the patients. Current therapies are restricted to operation and irradiation, often combined with a small number of standard-of-care chemotherapeutic drugs, preferentially for advanced tumour patients. Only very recently, newer targeted therapies have entered the clinics, including Cetuximab, which targets the EGF receptor (EGFR), and several immune checkpoint inhibitors targeting the immune receptor PD-1 and its ligand PD-L1. HNSCC tumour tissues are characterized by a high degree of intra-tumour heterogeneity (ITH), and non-genetic alterations that may affect both non-transformed cells, such as cancer-associated fibroblasts (CAFs), and transformed carcinoma cells. This very high degree of heterogeneity likely contributes to acquired drug resistance, tumour dormancy, relapse, and distant or lymph node metastasis. ITH, in turn, is likely promoted by pronounced tumour cell plasticity, which manifests in highly dynamic and reversible phenomena such as of partial or hybrid forms of epithelial-to-mesenchymal transition (EMT), and enhanced tumour stemness. Stemness and tumour cell plasticity are strongly promoted by Notch signalling, which remains poorly understood especially in HNSCC. Here, we aim to elucidate how Notch signal may act both as a tumour suppressor and proto-oncogenic, probably during different stages of tumour cell initiation and progression. Notch signalling also interacts with numerous other signalling pathways, that may also have a decisive impact on tumour cell plasticity, acquired radio/chemoresistance, and metastatic progression of HNSCC. We outline the current stage of research related to Notch signalling, and how this pathway may be intricately interconnected with other, druggable targets and signalling mechanisms in HNSCC.